Synthesis of large-area ultrathin graphdiyne films at an air–water interface and their application in memristors. (4th March 2020) - Li, Wanhui; Liu, Jie; Yu, Yanxia; Feng, Guangyuan; Song, Yaru; Liang, Qiu; Liu, Lei; Lei, Shengbin; Hu, Wenping
Abstract : A simple approach was developed to fabricate large-area homogeneous GDY films at an air/water interface; the obtained GDY films exhibit steady nonvolatile resistance switching behavior with excellent data retention capability and high on/off ratio. Abstract : In this work we present for the first time the nonvolatile resistive switching behavior of graphdiyne (GDY) film. We developed a simple approach to fabricate large-area homogeneous GDY films at an air/water interface, via catalytic homocoupling of hexaethynylbenzene at ambient temperature. The high uniformity, large size and low surface roughness of the as obtained GDY films to a large extent simplify the typical complex fabrication processes of carbon-based memristors. The rewritable memristors based on this ultrathin GDY film (about 7 nm) exhibit steady nonvolatile resistance switching behavior with excellent data retention capability (>10 3 s) and high on/off ratio (about 10 3 ). This is the first report on nonvolatile memristors based on pure continuous ultrathin GDY films which show clear write/erase switching properties. The electrical performances of the GDY memristors are significantly improved when Ag is used as a top electrode, which is likely due to the formation of Ag conductive filaments, as observed by HRTEM measurements. This study demonstrates that GDY films are promising candidates for carbon-based nonvolatile memristors.